Gambaran idiopathic osteosclerosis gigi molar ketiga impaksi pada radiograf Cone Beam Computed Tomography - Anak Agung Gde Dananjaya Agung; Ni Ketut Ayu Lestarini (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: To analyze idiopathic osteosclerosis radiographs associated with impacted third molars (M3) on cone beam computed tomography (CBCT). Case Report: A 36-year-old woman came to the Dentology Clinic complaining that the right mandibular third molar area often felt sore. The patient was referred for CBCT examination and incidentally, a radiopaque image with clear boundaries, irregular shape was found on the periapical impacted third molar without caries in the tooth crown. The treatment plan that will be carried out on the tooth is extraction. Conclusion: Idiopathic osteosclerosis lesions are lesions that occur in vital teeth that have the characteristics of a well-defined radiopaque appearance and are asymptomatic. Characteristics of idiopathic osteosclerosis lesions can be visualized by CBCT well. CBCT has the advantage of being able to display a detailed picture of the lesion in three dimensions (3D) with a fairly good image resolution.